Shade as an agro-management practice in Hevea seedling nursery in the North Eastern region - Gupta C; Krishna Kumar A K; Meenatoor J R; Pothen J; Potty S N; Sethuraj M R (1998)
An experiment with Hevea seedling nursery was conducted in Agarthala (W.Tripura) and Kolasib (Mizoram) of North Eastern region. Its objectives were to determine the influence of partial shade (40;light-cut) and three frequency of irrigation on the growth of Hevea seedlings. Provision of shade helped increasing the stem diameter of Hevea seedlings significantly than the unshaded ones. Shaded plots had more vigorous growth(stem diameter and plant height) than the unshaded. Frequency of irrigation did not have any significant influence on the stem diameter both in shaded as well as unshaded condition. Results from Mizoram reveals that shading has significantly improved the stem diameter of seedlings. The effect of frequency of irrigation also significant. Provision of shade helped in maintaining a higher plant population. The practical utility of this is availability of larger number of plants for green budding by February-March, so hat this can be polybagged to be planted during the same season. The results indicate that shade helps in vigorous growth as evidence by increased stem diameter and plant height. Shading also helped in making available more plants for green budding during Feb-March and also a higher percentage of buddable seedlings per unit area. This has a practical utility in the North Eastern Region so that the budded stumps available can be polybagged for planting during the same season.
Keywords: Budding success and percentage buddable plants; Frequency of irrigation; Green budding; Hevea; Partial shade; Seedlings